Different Mangrove Rehabilitation Statuses Effects to Benthic Bacterial Structure Community in the Northern Area of Java Island: Mangrove Rehabilitation to Benthic Bacterial in the Northern Area of Java Island - Vidayanti, Viky; Retnaningdyah, Catur; Mustafa, Irfan; Oktaviani, Indah (Journal of Tropical Life Science, 2024)
The study proposed identifying the changes in bacterial community and diversity and exploring the potential correlations among sediments parameters and benthic bacterial communities under different mangrove ecosystems rehabilitation statuses. There were three sites: 1. Banyuurip Mangrove Center (BMC) as a restoration site; 2. Pulau Lusi (PL) as a degraded site; and 3. Kampung Blekok (KB) as natural site. The physicochemical parameters and benthic bacteria from the mangrove sediment of the three locations were observed. The data were analyzed statistically to determine the sites' variation and the correlation between parameters. The results found that the physicochemical parameters among restoration sites varied. Soil organic matter (SOM) in natural and restoration sites was significantly higher than in degraded sites. Cation exchange capacity (CEC), calcium and potassium ions, and soil conductivity of the restoration site were considerably higher than the other sites. According to diversity indices and taxa richness, benthic bacteria in the restoration were the most diverse. Proteobacteria dominated in natural and restoration sites; meanwhile, Firmicutes dominated in degraded site. Sulfurovum aggregans was found abundant in natural and restoration sites; meanwhile, Mesobacillus subterraneus was the dominant species in the degraded site. Furthermore, the bacterial taxa richness was positively correlated with SOM and the bacterial diversity was correlated with CEC and conductivity.